Advances in Genetics of Regeneration in Metabesity - Gauthier, Benoit R. (Genes (Basel), 2019)
‘Metabesity’ is a recent term comprising a wide range of diseases with underlying metabolic disarrangements at its root, and whose aetiology lies in complex relationships among genes and the obesogenic environment to which individuals are currently exposed in most countries. Of note, epigenetic changes are increasingly being reported to play an outstanding role in carrying deleterious information that, together with susceptibility genes, boost the development of metabesity in subsequent generations. In this context, it is noteworthy to mention that the transition from the pre-industrial era to the current high-technology society and global economy, even after suffering two world wars, has been very fast. By contrast, evolution-driven processes, such as biological ones, are slow. In fact, there is a general consensus that at the metabolic level, adipogenic processes and thrifty pathways prevail over those promoting energy expenditure in a way that currently leads to metabolic diseases by excessive energy storage. In such an imbalanced social–biological scenario, genes that were beneficial in the past have shifted to becoming detrimental, i.e., favouring metabesity, which is quickly growing to reach pandemic proportions.